Effect of statin on perioperative myocardial injury in isolated valve surgery. (June 2021) - Kaushik, Atul; Kapoor, Aditya; Agarwal, Surendra Kumar; Pande, Shantanu; Kashyap, Shiridhar; Sinha, Archana; Khanna, Roopali; Kumar, Sudeep; Garg, Naveen; Tewari, Satyendra; Goel, Pravin K
Background: Statins have known pleiotropic effects that confer protection from ischemia-reperfusion injury. Because cardiopulmonary bypass is a potentially reversible ischemia-reperfusion sequence, we aimed to assess whether statin loading could help to limit myocardial injury in patients undergoing isolated heart valve replacement under cardiopulmonary bypass. Methods: One hundred patients with rheumatic valvular heart disease undergoing valve replacement received either a loading dose of rosuvastatin (40 mg initiated 7 days before surgery; loaded group) or no statins (non-loaded group). Cardiac troponin I, creatine kinase MB, and brain natriuretic peptide were measured at 8, 24, and 48 hours postoperatively. The primary endpoint was the extent of perioperative myocardial injury measured by the area under the curve for each biomarker. Results: Despite similar baseline levels, all biomarkers at 8, 24, and 48 h were significantly lower in the loaded group. The area under the curve of each biomarker was significantly lower in the loaded group than in the non-loaded group (troponin I: 31.43 vs. 77.21 ng·h·mL −1, creatine kinase MB 309.31 vs. 429.12 ng·h·mL −1, brain natriuretic peptide 5176.11 vs. 16119.31 pg·h·mL −1, all p < 0.001). The mean changes from baseline to peak levels were also significantly lower in the loaded group. The loaded group had a shorter hospital stay but no significant difference was seen in ventilator time, inotrope time, aortic crossclamp time, cardiopulmonary bypass time, or intensive care unit stay. Conclusion: In patients undergoing valve replacement, high-dose statin loading before surgery had a favorable impact on the release kinetics of various cardiac biomarkers.